VOPO4⋅2H2O Nanosheet Cathode for Enhanced Sodium Storage - Zhang, Xianghua; Yang, Dan; Liu, Weiling; Feng, Yuezhan; Rui, Xianhong; Yu, Yan (Frontiers in Energy Research, 2020)
Na-ion batteries (SIBs) are anticipated to capture a broad development space in the field of large-scale energy storage due to the abundant sodium resources. High-performance cathode materials are very critical. VOPO4·2H2O with a two-dimensional (2D) layered structure is a very promising candidate for SIBs because of its high working voltage and theoretical specific capacity. Herein, a simple one-step reflux method is designed to fabricate a cathode of VOPO4·2H2O nanosheets. It exhibits a high average operating potential of ~3.5 V, remarkable specific capacity (e.g.,135 mAh g-1 at 0.05 C), favorable high current charge-discharge ability (e.g., 58 mAh g-1 even at 20 C) as well as extralong cyclability (e.g., 0.026% capacity fading rate for per cycle at 20 C during 1000 cycles). The kinetic analysis implies that the superior sodium storage performance is mainly benefiting from the advantages of unique nanosheet structure, accelerating the rapid Na-ion diffusion.